Differences in Personal, Familial, Social, and School Factors Between Underachieving and Non-underachieving Gifted Secondary Students - Gilar-Corbi, Raquel; Veas, Alejandro; Miñano, Pablo; Castejón, Juan-Luis (Frontiers in Psychology, 2019)
Using various identification methods, differences between underachieving and non-underachieving gifted students in personal, familial, social, and school variables were analyzed in a sample of 164 gifted students with IQs of 120 or higher; the sample was drawn from a larger sample of 1,400 compulsory secondary education students. Three procedures for identifying underachieving students were used: the standardized difference method, the regression method, and the Rasch method. The different profiles of underachieving and non-underachieving students in the personal, familial, social, and school variables were compared using MANOVA and ANOVA tests. Results revealed that underachieving gifted students scored significantly lower in learning strategies, goal orientations, self-concept, attitudes toward teachers, and perceived parent involvement in school variables. These results have clear educational implications as a result of identifying differences in non-cognitive factors.